Oficina sobre o infinito: uma proposta didática para os alunos das séries finais do Ensino Fundamental II e Ensino Médio - Silva, Robson Luiza da (2016)
The purpose of this project is to offer complementary material for both basic education teachers (primary and secondary education) and students who are interested in having arguments (in this level of study) to work with the infinity and infinite series. Therefore, some demonstrations and examples which ground the topic were made. The concepts used were raised from references which are used by teachers and students from primary and secondary education. Algebraic and arithmetic arguments related to the infinity, such as recurring decimals and real numbers, were presented. Applications involving infinite series, like the generation of ?? and the approximation of some functions using infinite sums, were also shown. This material can be used as reference by techers and students who need additional material to learn about the topic.